Daily Triglyceride Kinetics When Consuming a Realistic Western Diet in At-risk Individuals Across the Metabolic Spectrum: A Case Study. (7th June 2021) - Keirns, Bryant; Sciarrillo, Christina; Poindexter, Kara; Emerson, Sam
Abstract: Objectives: Most of the day is spent in the postprandial state, in part because of the additive effect of dietary fat from meals on triglycerides (TG), and this response is exacerbated by insulin resistance. However, 24-hr TG kinetics when consuming a realistic, Western diet (WD) remain poorly defined in at-risk individuals. The purpose of this exploratory case study was to compare postprandial 24-hr TG in 3 at-risk individuals defined as having normal-weight obesity (NWO), metabolic syndrome (MetS), and type 2 diabetes (T2D) consuming a WD. Methods: 1 adult male from the following categories were recruited: NWO (i.e., 30% body fat and normal BMI), MetS (also a smoker), and T2D (taking 20 mg Atorvastatin). Upon arrival, a 24-guage indwelling catheter was inserted and a 0.9% NaCl drip initiated. Blood was drawn and TG measured hourly for 18-hrs and every 3-hrs for the last 6-hrs (Alere Cholestech; Hayward, CA). A semi-ad libitum WD (∼46% fat, 36% CHO, 18% protein) was provided consisting of breakfast (Jimmy Dean's), lunch 4-hrs later (McDonald's), dinner 5-hrs after lunch (Little Caesar's), and a snack 3-hrs after dinner (Blue Bell). Participants slept ≥ 6.5 hrs. Results: As expected, all participants' TG remained above fasting ≥ 75% of the 24-hr period and all exhibited peak TG between lunch and dinner. NWO presented with fasting TG of 100 mg/dL, and experienced peak TG of 278 mg/dL and area under the curve (AUC) of 3393 mg/dL. MetS similarly displayed a ∼3-fold increase in TG, although all TG parameters were lower (fasting = 69 mg/dL, peak = 214 mg/dL, AUC = 2772 mg/dL). Lastly, T2D closely resembled NWO with fasting TG of 100 mg/dL, peak TG of 282 mg/dL, and an AUC of 3165 mg/dL. Conclusions: In this case study, we observed that all 3 at-risk participants' TG nearly tripled from baseline despite markedly different body composition, risk factors, and health status. NWO and T2D both had an adverse postprandial response per current guidelines (i.e., ≥ 220 mg/dL), but MetS was just below this mark. Surprisingly, NWO had a very similar TG response to T2D and the greatest AUC, although the statin very likely mitigated postprandial TG in T2D. Future, larger studies should seek to confirm our observation that a wide range of at-risk individuals experience a deleterious postprandial TG response during daily living when consuming a WD. Funding Sources: Internal Sources at Oklahoma State University